PENENTUAN SEKTOR-SEKTOR UNGGULAN YANG ADA PADA KABUPATEN TAKALAR MELALUI ANALISIS TIPOLOGI KLASSEN - Rajab, Abdul; Rusli, Rusli (LPPM Universitas Muhammadiyah Mamuju, 2019)
This research essentially aims to determine the region's leading economic sector in Takalar District which can later be used as information material in economic development planning. The data used in this study are secondary data in the form of time series of the Gross Regional Domestic Product (GRDP) of Takalar Regency and South Sulawesi Province in 2013-2017, both based on the 2010 Constant Price and the Current Price. The analytical tool used in this study, namely the Klassen Tipology analysis. The results of the analysis show that based on the 2010 constant price the dominant sector of contribution is the Agriculture, Forestry and Fisheries sector with a value of 46.81%. Likewise based on the current prices of the sector, Agriculture, Forestry and Fisheries which have high contributions with a value of 49.25%,%. Based on the Klassen Tipology analysis, the sectors included in the potential category based on 2010 constant prices are the Mining and Excavation sector, the Water Procurement Sector, Waste, Waste and Recycling Management, the Retail and Trade sector; Car and Motorcycle Repair, Transportation and Warehousing sector and Information and Communication sector. Whereas the sectors included in the potential category based on current prices are the Mining and Excavation sector, the Water Procurement sector, Waste Management, Waste and Recycling, the Construction sector, the Provision of Accommodation and Drinking and the Information and Communication sector.